Pelatihan Duta UKS Dalam Meningkatkan Kesehatan Remaja Putri Di Boarding School Man 2 Surakarta - Tria Puspita Sari; Nevia Zulfatunnisa; Eko Nugroho; Angela Syifa Anindya Faadihilah Purwanto; Romadhani Putri Wahyuningtyas (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
The complex reproductive health issues faced by teenagers and the suboptimal implementation of the School Health Efforts (UKS) triad at the high school level have a significant impact on the health of students, particularly in improving reproductive health and promoting a clean and healthy lifestyle (PHBS). Madrasah Aliyah 2 Surakarta (MAN 2 Surakarta) is a private Islamic-based school in the city of Surakarta that has a Boarding School program for girls located not far from the main building. Based on observations, the condition of the UKS room in the girls' boarding school building does not meet the general UKS standards and the management of the UKS triad is not optimal. The aim of this community service is to improve UKS management facilities as a means of optimizing health improvement through trained UKS ambassadors. The method applied in this community service consists of Situational Analysis (Problems), Solutions, and Implementation of UKS Ambassador Training. The results of this community service show that the students were very enthusiastic about participating in the UKS ambassador training and there was an increase in knowledge before (pre-test 86.6%) and after (post-test 94.6%) training by 5%.